Using systems mapping within the process evaluation of a randomised controlled trial of the ACE active ageing programme in England and Wales - Helen Hawley-Hague; Colin Greaves; Diane Crone; Afroditi Stathi; Nick Cavill; Amy Davies; Katie E Chatwin; Zsofia Szekeres; Janet Withall; Janice Thompson (BMJ Public Health)
Background System mapping has mainly been used to develop theories and understanding of complex systems; to hypothesise how an intervention might work in a complex system or to inform intervention development. There are a few examples of the use of system mapping as part of process evaluation. In this paper, we describe an innovative approach to using system mapping as part of the process evaluation of a randomised controlled trial of the Active, Connected, Engaged (ACE) community-based active ageing programme.Method Ten participatory workshops were held across three of the ACE sites (Cardiff, Stoke-on-Trent and Manchester, UK). These involved over 100 participants, volunteers and stakeholders (from National Health Service, statutory and voluntary sectors). Their aim was to gather area-specific information on participants’ barriers and facilitators to physical activity and the needs of peer volunteers and service providers; and create ‘baseline’ system maps before the launch of the programme in the three areas of ACE delivery.Results System maps were produced showing the main outcome (physical activity) and the interactions between the key motivators and barriers described by older people, as well as ideas from stakeholders and volunteers about how these barriers can be addressed. Findings led to refinements to ACE intervention processes and the study’s logic model.Conclusions System mapping helped to refine the ACE processes and fine-tune the logic model. The value of this approach will increase in the next phase when it will be used to explore any changes to the physical activity system including changes to stakeholders’ ways of working and collaborating to tackle barriers to activity following the completion of the ACE trial.Trial registration number ISRCTN17660493.